The crustal structure of the central anatolia using receiver function analysis - Yelkenci, Seda. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2006., 2006)
Central Anatolia has complicated crustal and upper mantle structure that is influenced by the thermal and geodynamic process related to motions of surrounding plates. Few studies of the crustal structure of Central Anatolia have been done. Basically, studies of the nature of the crust have been performed for central Anatolia under the Calibration project started in 2002. To further investigate the crustal structure in the region, we present results from receiver function analysis using new data from temporary network which was installed under the same project. These temporary stations operated for period of one and half months between October and November, 2002. In addition, permanent stations ANTO, ISP and MALT were also used to compute receiver functions. Receiver function that is the seismic response of the Earth beneath the seismic station leads to investigation of tectonic and geodynamic processes. In this study, H-K stacking algorithm which gives crustal thicknesses and VpNs ratios as outputs of method has been used for receiver function analysis. Three component teleseismic data with epicentral distances between 30 and 103 degrees has been preferred to obtain single-event RFs and to investigate Moho depth under the Central Anatolia. Consequently, the structure of the region has been reasonably defined and compared with other geophysical studies. As a result of the RF analysis, although it has found that Moho depth decreases from about 43 km eastern part of central Anatolia to about 35 km western part, we observed sharp changes for some regions in which Tuz GOlti basin, central Anatolia core complex and !sparta that may prevent smooth changes in crustal thickness. Furthermore, we found almost high VpNs ratios that can indicate thermal structure in the study area. Additionally, we acquired information concerning the thickness of central Anatolia from relocating local earthquakes, which were recorded by the temporary stations during recording periods. Then obtained outcomes were discussed with results of RF analysis. In the light of this study, new treaties based on waveform modeling technique in the future can allow us getting detailed investigation concerning crustal structure of the Central Anatolia.
Keywords: Geology, Structural -- Turkey.; Seismology -- Turkey.